Aplikasi Pemesanan Ruang Karaoke Pada K2 Karaoke Berbasis Android - Trio Utomo (LPPM Universitas Al Washliyah Labuhanbatu, 2023)
The problem faced by K2 Karaoke so far is that the process of ordering karaoke rooms is done manually, namely customers must come directly to the location to make reservations for karaoke rooms and customers do not know the tariff information from the karaoke room on weekdays or weekends, thus it takes quite a long time to complete. the process of ordering a karaoke room, as well as the tariff is known by the customer when ordering a karaoke room occurs. There are also many places that specialize in booking karaoke rooms that can provide information for their customers in choosing and ordering karaoke rooms. The receptionist has difficulty in recaping orders from the karaoke room because there are too many consumers, especially on holidays and weekends. To overcome the problems mentioned above, a new system is needed in ordering karaoke rooms. The android-based karaoke room reservation application system is very appropriate to overcome these problems so that the karaoke room reservation process is carried out with Android and consumers can find out the availability of karaoke in full, payment processing and in full. Because the majority of people already have and are able to operate Android, so the process of ordering karaoke rooms can be done quickly and wherever they are and K2 Karaoke can directly receive orders from customers and obtain accurate karaoke room booking reports.